Total Quality Management Strategy for Improving the Quality of Education at Kolej Universiti Perguruan Ugama Seri Begawan (Empirical Study in the Arabic Language Education Master's Study Program) - Firdaus, M. Iqbal; Yusuf, Muhamad Hani; Nugroho, Wahyu; Fanani, Eiffan (STAI Auliaurrasyidin Tembilahan, 2024)
This research aims to determine the Total Quality Management (TQM) strategy for improving the quality of education in the Arabic Language Education Master's Study Program at Kolej Universiti Perguruan Ugama Seri Begawan (KUPU SB). This research uses a qualitative descriptive analysis method with a case study approach. Data was collected through interviews, observation, and documentation. The research results show that KUPU SB implements TQM by involving all parties, both internal and external, in improving the quality of education. TQM at KUPU SB includes aspects of vision and mission, information, human resources, facilities, competence, and loyalty. The implementation of TQM at KUPU SB has had a positive impact on the university, personnel, and graduates. Universities can compete at a global level, personnel can improve their welfare, and graduates can meet labor market needs. This study is novelty in the field of education quality regarding how KUPU provides facilities and support for activities to develop student potential.